(untitled) (Modern education and development, 2025)
This article discusses the origin of Taraxacum albidum, a species belonging to the Taraxacum genus within the Asteraceae family, Taraxacum albidum highlighting its distinct morphological characteristics that set it apart from other species, as well as its unique medicinal properties. Based on data presented in herbarium specimens, the article also outlines the dynamics of the species over the years.